Clinical reasoning in unimodal interventions in patients with non-specific neck pain in daily physiotherapy practice, a Delphi study. (October 2018) - Maissan, Francois; Pool, Jan; Stutterheim, Eric; Wittink, Harriet; Ostelo, Raymond
Abstract: Background: Neck pain is the fourth major cause of disability worldwide but sufficient evidence regarding treatment is not available. This study is a first exploratory attempt to gain insight into and consensus on the clinical reasoning of experts in patients with non-specific neck pain. Objective: First, we aimed to inventory expert opinions regarding the indication for physiotherapy when, other than neck pain, no positive signs and symptoms and no positive diagnostic tests are present. Secondly, we aimed to determine which measurement instruments are being used and when they are used to support and objectify the clinical reasoning process. Finally, we wanted to establish consensus among experts regarding the use of unimodal interventions in patients with non-specific neck pain, i.e. their sequential linear clinical reasoning. Study design: A Delphi study. Methods: A Web-based Delphi study was conducted. Fifteen experts (teachers and researchers) participated. Results: Pain alone was deemed not be an indication for physiotherapy treatment. PROMs are mainly used for evaluative purposes and physical tests for diagnostic and evaluative purposes. Eighteen different variants of sequential linear clinical reasoning were investigated within our Delphi study. Only 6 out of 18 variants of sequential linear clinical reasoning reached more than 50% consensus. Conclusion: Pain alone is not an indication for physiotherapy. Insight has been obtained into which measurement instruments are used and when they are used. Consensus about sequential linear lines of clinical reasoning was poor. Highlights: Pain alone was deemed not be an indication for physiotherapy treatment. PROMs are used for evaluative purposes, physical tests also for evaluative purposes. Consensus regarding the use of unimodal interventions in was poor.